SOSIALISASI SERTIFIKASI KOMPETENSI PROFESI PELATIH DAN ASISTEN PELATIH OLAHRAGA DI KABUPATEN INDRAMAYU JAWA BARAT - Ika Novitaria Marani; Ari Subarkah; Heni Widyaningsih (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
Abstract Professional certification aims to ensure a person's competence that has been obtained through learning, training, or work experience. Certification provided by professional organizations or associations provides a guarantee that the person holding it has obtained a certain competency standard. However, the function and benefits of this professional certification are not widely known by a profession. Likewise with sports coaches and assistant coaches in Indramayu Regency. Sports coaches and assistant coaches in Indramayu Regency do not yet know what and how professional certification is. Therefore, the solution is to provide socialization regarding professional certification of coaches and assistant coaches. So the purpose of community service activities is for the target audience to understand the function and benefits of having professional certification for coaches and assistant coaches. The training location is carried out in the university's fostered area, namely Indramayu Regency, West Java. The implementation time was in May 2024 at the BJB Bank Hall building, Indramayu Regency. The methods used in this socialization were lecture and discussion methods when delivering professional certification socialization materials. The results of community service activities show that there has been an increase in knowledge about the function and benefits of having professional certification for coaches and assistant coaches. So it is hoped that all sports coaches and assistant sports coaches in Indramayu district have professional competency certification and are declared competent.   Abstrak Sertifikasi profesi bertujuan untuk memastikan kompetensi seseorang yang telah didapatkan melalui pembelajaran, pelatihan, maupun pengalaman kerja. Sertifikasi yang diberikan organisasi atau asosiasi profesi memberikan jaminan bahwa orang yang menyandangnya telah mendapatkan standar kompetensi tertentu. Namun, sertifikasi profesi ini belum banyak diketahui fungsi dan manfaatnya oleh suatu profesi. Begitu pula halnya dengan para pelatih dan asisten pelatih olahraga di Kabupaten Indramayu. Para pelatih dan asisten pelatih olahraga di Kabupaten Indrmayu belum mengetahui apa dan bagaimana sertifikasi profesi itu. Oleh karena itu, solusinya diberikan sosialisasi terkait sertifikasi profesi pelatih dan asisten pelatih olahraga. Sehingga tujuan dari kegiatan pengabdian kepada Masyarakat adalah agar khalayak sasaran memahami tentang fungsi dan manfaat dari memiliki sertifikasi profesi pelatih dan asisten pelatih olahraga. Tempat pelatihan dilakukan di wilayah binaan universitas yaitu Kabupaten Indramayu Jawa Barat. Waktu pelaksanaan dilakukan pada bulan Mei 2024 di gedung Aula bank BJB Kabupaten Indramayu. Metode yang digunakan dalam sosialisasi ini adalah metode ceramah dan diskusi saat menyampaikan materi sosialisasi sertifikasi profesi. Hasil kegiatan pengabdian menunjukkan bahwa terjadi peningkatan pengetahuan tentang fungsi dan manfaat dari memiliki sertifikasi profesi pelatih dan asisten pelatih olahraga. Sehingga diharapkan semua pelatih olahraga dan asisten pelatih olahraga di kabupaten Indramayu memiliki sertifikasi kompetensi profesi dan dinyatakan kompeten.